Diaqua-(oxydiacetato-3 O,O′,O″)(pyridine-3- carboxamide-N 1)copper(II) - Perec, Mireille (2009)
In the mononuclear title compound, [Cu(C4H4O 5)(C6H6N2O)(H2O) 2], the CuII centre is bound to a chelating oxydiacetate ligand, a monodentate pyridine-3-carboxamide unit and two water mol-ecules, defining an octa-hedral coordination where the first two ligands form the equatorial plane and the last two occupy the apical sites. The planar oxydiacetate ligand is slightly disordered at its central ether O atom. The availability of efficient donors and acceptors for hydrogen bonding results in a complex inter-action scheme where each monomer links to six similar units to define a well connected three-dimensional structure. A comparison is made with related structures in the literature, and the reasons for their differences are discussed.